Digital Culture and Physical Education: questioning the inclusion of Exergames in the curriculum - César Augusto Otero Vaghetti; Karina Longone Vieira; Silvia Silva da Costa Botelho (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
Games are known to be used in education, as teaching tools, because they can facilitate cognitive learning. Several areas such as Mathematics, Geography, History, Chemistry and Biology use this technology in reason of its illustrative potential on the content to be worked, something that many games make possible. Moreover, one of the most important aspects to be considered is the communication established between educator and learner, in which pleasure and entertainment are inherent features of the game, thus pleasing the student and enabling learning. Currently, a new class of games is taking the attention of children, young people and adults: the Exergames or Exertion Interfaces, which mix game and physical exercise. Not only as new educational tools that become available but also some attention concerning physiological and educational aspects for the human development begin to be demanded from areas like Health Sciences, especially Physical Education. This research aimed at discussing, in a critical way, issues related to the Exergames and the possibility for them to be included in the curriculum of Physical Education, both at school and in the undergraduate and graduate courses. Keywords: Exergame, Physical Education, Curriculum.